The art of partnership: Expanding representations and interpretations - Cook-Sather, Alison; Slates, Sarah Elizabeth; Bala, Nandeeta; Amer, Adan; Anthony, Holly; Cachia, Chris; Cassidy, Alice; Freer Conley, Cindy; Costello, Katie; DeVita, James M.; Souto Galvan, Ana; Howells, Michaela; et al. (International Journal for Students as Partners, 2022)
NA